2004
DOI: 10.2460/ajvr.2004.65.289
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of leukotriene B4 production in leukocytes from horses with recurrent airway obstruction

Abstract: Results suggested increased production of LTB4 in airways of RAO-affected horses, compared with control horses, that may contribute to the infiltration of neutrophils into the lungs and the sustained inflammation associated with RAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…For BAL performed 24 h after nebulization, an adjacent airway was lavaged to that sampled 10 min after nebulization to minimize the effects of the previous BAL on BALF cytology. Sweeney et al (37) demonstrated that any effects of a BAL on BALF cytology from an adjacent airway were eliminated within 48 h. Repeating the BAL procedure after 6 and 24 h on different lung regions did not significantly alter BALF cytology in healthy horses (25). Similarly, in the present study, BALF neutrophil numbers were only significantly elevated in the RAO group and not in the control horses 24 h after nebulization and BAL of an adjacent airway.…”
Section: Discussionsupporting
confidence: 38%
“…For BAL performed 24 h after nebulization, an adjacent airway was lavaged to that sampled 10 min after nebulization to minimize the effects of the previous BAL on BALF cytology. Sweeney et al (37) demonstrated that any effects of a BAL on BALF cytology from an adjacent airway were eliminated within 48 h. Repeating the BAL procedure after 6 and 24 h on different lung regions did not significantly alter BALF cytology in healthy horses (25). Similarly, in the present study, BALF neutrophil numbers were only significantly elevated in the RAO group and not in the control horses 24 h after nebulization and BAL of an adjacent airway.…”
Section: Discussionsupporting
confidence: 38%
“…22 One study 12 reported that the percentages of neutrophils in BALF of RAO-affected horses when asymptomatic were 14.0 6 2.7% but increased to 41.7 6 9.5% when horses were exposed to hay dust for 2 weeks, during which time clinical signs of RAO developed. Another study 16 reported that the percentages of neutrophils in BALF of RAO-affected horses pre-and poststabling were 15.0 610.0% and .60%, respectively. In a third study, 1 when RAO-affected horses were housed in a natural challenge environment (stabled, fed dusty hay), the percentages of neutrophils in BALF were increased 4-to 6-fold (52 6 8%) compared with healthy horses (8 6 1%).…”
Section: Discussionmentioning
confidence: 99%
“…18 Authors of another study concluded that increased concentrations of LTB 4 in airways of RAO-affected horses contributes to neutrophil infiltration and the ongoing inflammation associated with RAO. 16 In humans, histamine stimulation of bronchial epithelial cells involves binding at H1 receptors, production of LTB 4 , activation of the transcription factor NF-kB, and increased expression of IL-8. 2 Activity of NF-kB is increased in bronchial cells of RAO-affected horses and is highly correlated to the percentage of neutrophils present in the bronchi.…”
Section: Discussionmentioning
confidence: 99%
“…Other cells, such as BAL cells (3), airway smooth muscle cells (34), endothelial cells (20), and monocytes (10), also release IL-8 upon stimulation. Also, other neutrophil chemotactic agents such as leukotriene B 4 , TNF-␣, granulocyte/macrophage colony-stimulating factor (GM-CSF), complement activation, and reduced apoptosis (16,25,44) may contribute to airway neutrophilia. A20, overexpressed in other animal models, inhibits NF-B activation, thereby decreasing LPS-induced IL-8 production (15).…”
Section: Discussionmentioning
confidence: 99%